2008
DOI: 10.1039/b800143j
|View full text |Cite
|
Sign up to set email alerts
|

Novel iron titanate catalyst for the selective catalytic reduction of NO with NH3 in the medium temperature range

Abstract: An iron titanate catalyst with a crystallite phase, prepared by a co-precipitation method, showed excellent activity, stability, selectivity and SO 2 /H 2 O durability in the selective catalytic reduction of NO with NH 3 in the medium temperature range.Nitrogen oxides (NO x ) have become a major source of air pollution which can result in photochemical smog, acid rain and ozone depletion and have strong respiratory toxicity endangering human health.1 Stringent environmental legislation has been made worldwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 17 publications
4
103
0
2
Order By: Relevance
“…Previous research reported that Fe-Ti mixed oxide was a novel catalyst for the selective catalytic reduction of NO with NH 3 in the medium temperature range (200-400°C) which was placed after the flue gas desulfurization (FGD). 58 In our future work, (Fe 2 Ti) 0.8 O 4 will be investigated to control the emission of NO x . If (Fe 2 Ti) 0.8 O 4 is an excellent catalyst for the control of NO x emission, it will be mainly used to control the emission of NO x , and elemental mercury will be captured as a cobenefit.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research reported that Fe-Ti mixed oxide was a novel catalyst for the selective catalytic reduction of NO with NH 3 in the medium temperature range (200-400°C) which was placed after the flue gas desulfurization (FGD). 58 In our future work, (Fe 2 Ti) 0.8 O 4 will be investigated to control the emission of NO x . If (Fe 2 Ti) 0.8 O 4 is an excellent catalyst for the control of NO x emission, it will be mainly used to control the emission of NO x , and elemental mercury will be captured as a cobenefit.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction between iron, manganese and titanium species led to a highly dispersive state of active phases, without forming iron oxides, manganese oxides or titanium oxide particles. In our previous study [5,6], we have concluded that the FeTiO x catalyst was mainly in the form of crystallite phases of Fe 2 TiO 5 and FeTiO 3 with specific Fe-O-Ti structure which showed high SCR activity. The substitution of Fe by Mn did not destroy the crystallite structures; furthermore, some crystallites with Mn-O-Ti and Fe-O-Mn structures might also be formed, because either FeMnTiO 4 or MnTiO 3 also has some diffraction peaks in the positions of the broad bumps.…”
Section: No and Nh 3 Oxidation Activities Of Fe A Mn 1àa Tio X Catalystsmentioning
confidence: 96%
“…Because of some inevitable disadvantages in practical application, such as the narrow operation temperature window [2], high conversion of SO 2 to SO 3 at high temperatures [3] and the toxicity of vanadium pentoxide to environment and human health [4], more and more researchers are focusing on the development of new SCR catalysts. In our previous study [5,6], we have developed an environmentally friendly novel iron titanate catalyst in crystallite phase with specific Fe-O-Ti structure, which showed excellent SCR activity, N 2 selectivity and H 2 O/SO 2 durability in the medium temperature range. However, the catalytic activity was not high enough for the application in denitrogenation of exhaust gas with low temperature, such as the flue gas after dust removal and desulfurization from coal-fired power plants and the exhaust gas from diesel engines in cold-start process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts should be made for the development and industrial application of environmentally benign NH3-SCR catalysts for controlling NOx emissions from diesel engines. In our previous studies, we developed several easily prepared Ce-based [17,18] and Fe-based [25] oxide catalysts and a Cu-SSZ-13 [13] small pore zeolite catalyst with excellent NH3-SCR performance. The CeWOx catalyst has already been studied for industrial application.…”
Section: Engine Bench Testsmentioning
confidence: 99%
“…However, the toxicity of vanadium species together with the narrow operation temperature window has limited the practical application of vanadium-based catalysts. Accordingly, some transition metal exchanged zeolites, e.g., Fe-ZSM-5 [7][8][9], Cu-SSZ-13 [10][11][12][13], and Cu-SAPO-34 [14][15][16], and vanadium-free oxide catalysts, e.g., Ce-based [17][18][19][20][21][22][23][24], Fe-based [25][26][27], and Cu-based [28] oxides, have been studied as potential substitutes of vanadium-based catalysts for diesel vehicles. However, the quality of the diesel fuel in China is still relatively low, and the sulfur content in the diesel fuel is often rather high.…”
Section: Introductionmentioning
confidence: 99%